Design, Synthesis and Biological Evaluation of Novel 5‐Phenyl‐5‐(thiophen‐2‐yl)‐4H‐1, 2, 4‐triazole‐3‐thiols as an Anticancer Agent. Issue 13 (7th April 2021) - Patel, Krupa R.; Brahmbhatt, Jpan G.; Pandya, Pranav A.; Bhadresha, Kinjal; Daraji, Drashti G.; Patel, Hitesh D.; Rawal, Rakesh M.; Baran, Sujit K.; Jayanthi, Sivaraman
Abstract: Tumor suppressor protein p53 is one of the most appealing targets for targeted anticancer therapy, due to its significant role in cancer prevention and abundant mutation in human cancers. A novel series of 4‐phenyl‐5‐(thiophen‐2‐yl)‐4 H ‐1, 2, 4‐triazole‐3‐thiols having ability to liberate p53 function by interrupting p53‐MDM2 interaction were successfully discovered by structure‐based designing approach and the principle of bioisosterism. In silico modules predicted that these small molecule inhibitors comprising 1, 2, 4‐triazole‐3‐thiol scaffold have draggability and ability to mimic critical binding residues of p53. To verify this hypothesis, we have synthesized and evaluated all designed compounds for their in vitro antiproliferative activity against A549, U87 and HL60 cell lines. Fourteen out of fifteen compounds exhibited good in vitro inhibitory activity in lower micromolar values. Particularly, compound F10 possessed excellent antitumor activity with IC50 values 1.029, 5.193 and 9.292 μM against three tested cell lines. IC50 value of potent analogous F10 in A549 cells decreases to 0.908 and 0.816 μM after 48 and 72 hours of incubation, respectively. Compound F10 represents a novel and promising lead structure for the development of antitumor agents as MDM2‐p53 interaction disruptors. Abstract : Bioisosterism concept & Structure‐based drug designing approach was used to identify highly potent 4‐phenyl‐5‐(thiophen‐2‐yl)‐4 H ‐1, 2, 4‐triazole‐3‐thiols with an ability to disturb p53‐MDM2 interaction in cancer cells. Compounds were characterized by spectroscopic methods including X‐ray crystal structure determination and assayed for their in vitro antiproliferative activity against A549, U87 and HL60 cell lines. Targeted molecules show good in vitro inhibitory activity in micromolar range. Compound F10 had excellent antitumor activity with IC50 values 1.029, 5.193 and 9.292 μM against three tested cell lines.